Peningkatan Hasil Belajar Peserta Didik pada Materi Kalor melalui Model Problem Based Learning - Dedy Hidayat; Abdul Muis; Dahniar Dahniar (Universitas Negeri Makassar, 2023)
This study aims to determine the implementation of the Problem Based Learning model in improving student learning outcomes on the material of heat and its transfer. This study uses a qualitative approach with the type of classroom action research. The subjects of this study were all 17 students of class 7A of SMP Negeri 4 Tanjung Palas Timur in the odd semester of the 2021/2022 academic year. Data collection was carried out through observation sheets of learning activities and learning outcome test items. The results of the study showed an increase in student learning outcomes on the material of heat and its transfer. The average value of students was 68.06 in cycle I, 71.94 in cycle II and increased to 81.65 in cycle III. The completeness of learning outcomes classically in cycle I was 47%, 71% in cycle II and in cycle III increased to 88%.